Algorithm for Fault Location and Classification on Parallel Transmission Line using Wavelet based on Clarke’s Transformation - Makmur Saini; A. A. Mohd Zin; M. W. Mustafa; A. R. Sultan; Rusdi Nur (Institute of Advanced Engineering and Science, 2018)
This paper proposed a new algorithm for fault location and classification using wavelet based on Clarke’s transformation to obtain the fault current. This novel method of fault current approach is studied by comparing the use of the glide path of the fault voltage. The current alpha and beta (Current Mode) were used to transform the signal using discrete wavelet transform (DWT). The fault location was determined by using the Clarke’s transformation, and then turned into a wavelet, which was very precise and thorough. The most accurate was the mother wavelet Db4 which had the fastest time and smallest error detection when compared with the other wavelet mothers. In this study, the Clarke’s transformation is also compared with the Karenbauer’s, which has produced results with similar error percentage. The simulation results using PSCAD / EMTDC software showed that the proposed algorithm could distinguish internal and external faults to get the current signal in the transformation of a signal fault.